KOMUNIKASI KRISIS DAN LEGITIMASI PEMERINTAH: ANALISIS WACANA KRITIS PERNYATAAN PEJABAT PUBLIK DALAM BENCANA BANJIR DAN LONGSOR DI SUMATERA NOVEMBER-DESEMBER 2025 - Syafira Natasya (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study examines how the language used by public officials in disaster situations constructs the meaning of crisis, shapes public perception, and affects government legitimacy. It is grounded in the phenomenon of officials’ communication that sparked public debate during the floods and landslides that struck Sumatra particularly Aceh, North Sumatra, and West Sumatra between late November and December 2025. The study employs Critical Discourse Analysis based on Norman Fairclough’s model, which consists of three dimensions: text, discursive practice, and social practice. The findings reveal that the choice of words, metaphors, and communication style of officials tend to frame the crisis in administrative and rational terms, which may shift attention away from the lived experiences of victims. At the level of discursive practice, officials’ statements are reproduced by the media and debated in the public sphere, generating multiple interpretations. Meanwhile, at the social level, tension emerges between public expectations of empathy and the way the state communicates the crisis. These results indicate that crisis communication is not merely about delivering information, but also about addressing emotional concerns and fostering a connection with the public. When empathy is not adequately conveyed, the distance between the government and society tends to widen, ultimately affecting public trust. Therefore, this study emphasizes the importance of more responsive, humane, and context-sensitive communication practices in maintaining government legitimacy during times of crisis.